Development of a Quality Care Plan to Reduce Otolaryngologic Readmissions: Early Lessons from the Cleveland Clinic. (12th February 2015) - Rajasekaran, Karthik; Revenaugh, Peter; Benninger, Michael; Burkey, Brian; Sindwani, Raj
Abstract : Objectives: Hospital readmissions are an important focus of national quality and cost containment efforts. With increased emphasis on the impact of unplanned readmissions, it is critical to evaluate factors contributing to readmission rates and optimize strategies aimed at reducing these rates. The objectives of this study were to discuss quality interventions implemented at our institution and to evaluate their impact on reducing readmissions. Study Design: Case series with chart review. Setting: Academic tertiary care medical center. Methods: Medical records of patients who were admitted to an otolaryngology inpatient service and readmitted within 30 days of discharge between January 2010 and December 2012 were reviewed. A quality care plan (QCP) was developed, and various interventions were implemented during this time to affect these rates. Results: There were 769, 816, and 798 admissions during the years 2010, 2011, and 2012, respectively. The number of readmissions during this time were 50 (6.5%), 51 (6.3%), and 28 (3.5%), respectively. There were no statistically significant differences in case mix index, demographics, and subsequent length of stay for those patients requiring readmission. The reduction in number of readmissions in 2012, after the institution of our QCP, was statistically significant ( P <. 05). Conclusion: Readmission within 30 days in a large otolaryngology practice can be multifactorial. To reduce rates of readmission, it is essential to understand the diagnoses, postoperative complications, and comorbidities contributing to readmission. Implementation of a QCP composed of comprehensive discharge planning and close postdischarge follow‐up can lead to a reduction in readmissions.